CHARACTERISTICS OF THE PERIOD CHANGES INMIRA-TYPE VARIABLES - Marsakova, V. I. (Одеські астрономічні публікації, 2014)
The period changes in a sample of Miraty pe variables were analysedand classified. Characteristics of the long-term cyclicity in the period changes were obtained.